Factors Influencing Resistance to Change Among Employees - Gunalan, Pasubathy (2010)
This study examines the factors that influence resistance to change in a business organization. Four factors were selected to test the possibility of having a simple but comprehensive model that can predict resistance to change. Due to the need for researchers to narrow down the scope of their research, there is lack of researches on change resistance which comprehensively cover the core antecedents that causes resistance to change from employee perspectives. The four factors; namely Perceived Personal Impact, Perceived Outcome for Organization, Trust In Management and Change Communication were hypothesized to significantly predict resistance to change. A survey questionnaire was chosen as the instrument of choice to collect the data for this study. Collected data was entered into SPSS 12.0 for statistical analysis. The data was then analyzed using Pearson Correlation Analysis and Multiple Regression Analysis to test the hypotheses. All four factors were found to have a relationship with resistance to change. However, only Perceived Personal Impact and Trust in Management were found uniquely contributing towards the prediction of resistance to change. The key to effectively managing change resistance is to clearly understand the nature and reasons for resistance. The findings from this research helps to understand how change resistance antecedents relates to one another that results in resistance to change at workplace.